BHAGAWATIMAH CIDYA DEWI: IDENTIFIKASI FIGUR WANITA MENGGENDONG BAYI DALAM PRASASTI CEBONGAN - Kayato Hardani (Balai Arkeologi Yogyakarta, 2009)
Some historical-archaeological remains from Java in 9th-10th century such as inscriptions have been preserved in good condition. Most of them has been transliterated and documented on systematically corpus or catalogues. The inscriptions which incised on stone or chopper were issued by the king who reigned in Java on that time, usually to commemorate the establishment of a free-hold land or cultivation area. Social-cultural lifehood sometimes reflected from the inscriptions. Only a few can be classified as spell or 'mantra' inscription. Besides old Java writing, human figurines is also described on the the chopper inscription. She is Bhagawatimah Cidya Dewi, divine body with a baby on her arms. There are some correlations found between the description of the figurines with the verbal contents of the inscription.